2021
DOI: 10.3390/medicina57080812
|View full text |Cite
|
Sign up to set email alerts
|

The Patient-Reported Outcome Measures Used with Low Back Pain and the Attitude of Primary Healthcare Practitioners in Saudi Arabia toward Them

Abstract: Background and objectives: The use of appropriate outcome measures can help guide multidimensional low back pain (LBP) management, elucidate the efficacy/effectiveness of interventions, and inform clinicians when selected targets have been achieved and this can be used for educational or research purposes. Aim: This study aimed to explore and describe the use, attitudes, knowledge, and beliefs regarding patient-reported outcome measures used by healthcare practitioners practising in Saudi Arabia who are freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 40 publications
1
12
0
Order By: Relevance
“…The majority of Egyptian physical therapists reported that they always assess their patients before treatment; however, the majority of them reported that they do it without using standard tools [16]. Another study showed that physiotherapists in Saudi Arabia frequently use outcome measures in their clinical management of patients with low back pain [18]. Another study showed that various outcome measures are used to a low-to-very-low extent when dealing with patients with low back pain [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of Egyptian physical therapists reported that they always assess their patients before treatment; however, the majority of them reported that they do it without using standard tools [16]. Another study showed that physiotherapists in Saudi Arabia frequently use outcome measures in their clinical management of patients with low back pain [18]. Another study showed that various outcome measures are used to a low-to-very-low extent when dealing with patients with low back pain [9].…”
Section: Discussionmentioning
confidence: 99%
“…For example, language and cultural barriers, the degree of organizational support received in their practice, [15] the patient's difficulty in understanding the outcome measures, [22] lack of clear guidance about the suitability of available outcome measures, lack of appropriate outcome measure, [11] lack of time and knowledge, [14] and lack of a routine for using outcome measures also was an identified barrier [21]. This highlights a need for professional training on the use of standardized outcome measures related to LBP [18].…”
Section: Discussionmentioning
confidence: 99%
“…Primary healthcare is associated with reducing big healthrelated issues, and it plays a role in improving the way of life. This particular study was conducted in India, and the general public was selected for the interview, where the objectives of the research were focused [16]. It was concluded that the physiotherapists engage the public of an area and take of their health and try to keep them healthy.…”
Section: Review Of Literaturementioning
confidence: 99%
“…On the other hand, they determine the health-related issues that exist in society, and they try their levels best to beat the arising health issues and try to maintain the health of the people in the proper order [16].…”
Section: Review Of Literaturementioning
confidence: 99%
“…Translated, cross-culturally adapted and validated versions of PROMs are increasingly utilized in spine research in Arab countries [ 19 - 48 ]. Matters such as understanding, experiences, religious beliefs, and expectations of patients and primary healthcare practitioners have also been looked into in recent publications [ 49 , 50 ]. None of the tools identified here was included amongst the 26 instruments listed in the recent systematic review that reported an assortment of PROMs in Arab-speaking populations [ 1 ].…”
Section: Reviewmentioning
confidence: 99%